Direct bladder hernia after indirect hernia repair in extremely low birth weight babies: two case reports and a review of the literature. (December 2017) - Tröbs, R.; Yilmaz, B.; Roll, C.; Alrefai, M.
Abstract Background Inguinal hernia repair is the most common surgical procedure in babies. Despite a meticulous technique, relapses may occur. The occurrence of a direct bladder wall hernia in relapses has never before been reported in the literature. Case presentation Here, we report two cases of direct bladder herniation: a white baby boy born after 25 weeks of gestation and a white baby boy born after 26 weeks of gestation. Both of the formerly extremely low birth weight babies were affected after open bilateral hernia repair. Recurrent hernias developed on the right side, and direct bladder herniation was identified intraoperatively. In one case, laparoscopy was applied to identify a supravesical type of hernia. Immaturity and a difficult postnatal course might have contributed to hernia relapse in these cases. Conclusions Misinterpretation of bladder herniation might have disastrous consequences. Laparoscopy is a helpful tool in comparable cases.